Guest

Derivation for the height of the tower when the body is projected vertically upwards from the top of the tower

Derivation for the height of the tower when the body is projected vertically upwards from the top of the tower 
 

Grade:12th pass

1 Answers

Toshika Choyal
askIITians Faculty 20 Points
4 months ago
Hi
Here’s the solution of your question

When the body is projected vertically upward ,

u = u

v = 0

a = g

t = u /g

Hmax = u² / 2g

Then the body starts falling freely

u = 0

v = v

H = Hmax + height of tower

a = g


Thanks
Regards

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free